PENGARUH PENGGUNAAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS - Wulandari, Puput; Muhammadi, Muhammadi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The study aims to determine the effect of model CTL to the learning outcomes in Social Science Class V at SD N 14 Balai Ahad Agam,in the even semester of the academic year 2018/2019. This research is a quantitative reseach with experimental This research is a quantitative research with experimental type and quasy experimental research design. Sampling data is taken by purposive sampling. The sample of this study amounted to 40 people, with a population of 40 people. Based on the research that has been done, obtained t count> t table, 2,13095 > 1,68595 with α = 0.05 is means Ho is rejected and Ha accepted, it meaning there is influence the use of Contextual Teaching and Learning (CTL) model of student learning outcomes in Social Science Class V SD N 14 Balai Ahad Agam.